A Conservation Overview of Gaps in Traditional Trade Skills in Australia. Issue 2 (3rd July 2019) - Dunn, Bronwyn; Sloggett, Robyn; Draayers, Wendy
Abstract : In 2003, the General Conference of UNESCO adopted the Convention for the Safeguarding of Intangible Cultural Heritage; recognising the important role traditional craftmanship has as a tangible manifestation of intangible heritage and highlighting the importance of the intergenerational transmission of knowledge and skills. Within this context, a Conservation Skills Gaps survey was conducted in 2016 that examined whether there was a current perceived skills gap relating to traditional trades; what difficulties might conservators have in accessing these trades; and, how such a skills gap might be addressed? This paper examines the results of this survey, reviews the 2000 AICCM Skills Gap Audit and the 2018 Heritage Skills Initiative Sector Analysis Survey that reported on the health of traditional trade skills in Australia, and discusses recent initiatives to revitalise rare trades. It also examines current work in developing opportunities to build intergenerational knowledge transfer, support specialist practitioners, and generate solutions to address skill gaps in traditional trades and conservation.